Advantages and limitations of virtual online consultations in a NHS acute trust: the VOCAL mixed-methods study - Shaw, S; Wherton, J; Vijayaraghavan, S; Morris, J; Bhattacharya, S; Hanson, P; Campbell-Richards, D; Ramoutar, S; Collard, A; Hodkinson, I; Greenhalgh, T (National Institute for Health Research, 2018)
Background: There is much enthusiasm from clinicians, industry and government to utilise digital technologies and introduce alternatives to face-to-face consultations. Objective(s): To define good practice and inform its implementation in relation to remote consultations via SkypeTM and similar technologies. Design: Multi-level mixed-method study of remote video consultations (micro-level) embedded in an organisational case study (meso-level), taking account of national context and wider influences (macro-level). Setting: Three contrasting clinical settings (diabetes, antenatal diabetes, cancer) in a National Health Service (NHS) acute trust. Data collection and analysis: Macro-level—interviews with 12 national-level stakeholders combined with document analysis. Meso-level—longitudinal organisational ethnography comprising over 300 hours of observations, 24 staff interviews and analysis of 16 documents. Micro-level— 30 video-recorded remote consultations; 17 matched audio-recorded face-toface consultations. Interview and ethnographic data were analysed thematically and theorised using strong structuration theory. Consultations were transcribed verbatim and analysed using the Roter Interactional Analysis System (RIAS), producing descriptive statistics on different kinds of talk and interaction. Results: Policymakers viewed remote video consulting as a way of delivering healthcare efficiently in the context of rising rates of chronic illness and growing demand for services. But the reality of establishing such services in a busy and financially stretched NHS acute trust proved far more complex and expensive than anticipated. Embedding new models of care took much time and resources and required multiple ‘workarounds’. Considerable ongoing effort was needed to adapt and align structures, processes and people within clinics and across the organisation. For practical and safety reasons, virtual consultations were not appropriate for every patient or every consultation. By the end of this study, between 2 and 20 percent of all consultations were being undertaken remotely in participating clinics. Technical challenges in setting up such consultations were typically minor but potentially prohibitive. When clinical, technical and practical preconditions were met, virtual consultations appeared safe and were popular with both patients and staff. Compared with face-to-face consultations, virtual consultations were very slightly shorter; patients did slightly more talking; and both parties sometimes needed to make explicit things that typically remained implicit in a traditional encounter. Virtual consultations appeared to work better when clinician and patient knew and trusted each other. Some clinicians used Skype™ adaptively to support ad hoc clinician-initiated and spontaneous patient-initiated encounters. Other clinicians chose not to use the new service model at all. Conclusions: Virtual consultations appear to be safe, effective and convenient for patients who are preselected by their clinicians as ‘suitable’, but such patients represent a small fraction of clinic workloads. There are complex challenges to embedding virtual consultation services within routine practice in the NHS. Roll-out (across the organisation) and scale-up (to other organisations) is likely to require considerable support. Limitations: The focus on a single NHS organization raises questions about the transferability of findings, especially quantitative data on likely uptake rates. Future research: Further studies on the micro-analysis of virtual consultations and on the spread and scale-up of virtual consulting services are planned. Funding: NIHR Health Services and Delivery Research programme (13/59/26)